Exome sequencing of pashtun familial epilepsy in Pakistan reveals novel variants in LAMA5, KCNQ2 and GNAO1 - Qaisar Ali; Sadiq Azam; Jamila Javed; Muhammad Zaheer; Saqib Ullah; Aqib Iqbal; Ibrar Khan; Shoaib Ur Rehman (Molecular Biology Reports, 2026)

CRIP1 knockdown enhances glycolytic dependence and increases sensitivity to 2-Deoxy-D-Glucose in acute myeloid leukemia - Muhammad Asif Zeb; Faryal Mehwish Awan; Aamir Ali Khan; Sadiq Noor Khan (Molecular Biology Reports, 2026)

Green mobility with battery electric buses: a review of transition and circularity integration - Syed Naveel Hussain; Kasun Hewage; Muhammad Zahid; Rehan Sadiq (Travel Behaviour and Society, 2026)

Antibiofilm efficacy and genomic characterization of a lytic bacteriophage targeting MDR uropathogenic Escherichia coli - Muhammad Hassan; Iqbal Ahmad Alvi; Sadiq Noor Khan; Dawood Ahmed; Muhammad Asif; Afshan Saleem; Abdul Jabbar (Archives of Microbiology, 2026)

Novel Hybrid Material as a Robust Photocatalyst for Degradation of Aqueous Phenolic Contamination - Bushra Bostan; Saima Sadiq; Inam Ullah; Makkah Zaman; Mian Muhammad; Muhammad Sadiq (Water, Air, & Soil Pollution, 2026)

Cortinarius squamibrunneus sp. nov. ( Basidiomycota ; Agaricales ) in C . Section Safranopedes of Subgenus Telamonia from Swat District, Khyber Pakhtunkhwa, Pakistan - Hira Ijaz; Tasneem Ashraf; Muhammad Naveed; Gul Sanga; Sadiq Ullah; Sana Jabeen (New Zealand Journal of Botany, 2026)
Cortinarius squamibrunneus sp. nov. was collected from Swat District, Khyber Pakhtunkhwa, Pakistan. The species is distinguished from its closely related species, C . epipurrus , by its pale orangish‐brown to brown, fibrillose–squamulose pileus with a darker central disc and a rimose to radially cracked margin, smaller basidiospores (5.5–7.4 × 3.6–5 μm) with finely ornamented warts and variably shaped sterile cells. Comparative morphological analyses combined with molecular phylogenetic inference based on the ITS region of nrDNA confirm that this taxon is distinct from previously described species and represents a new species within C. sect. Safranopedes of C . subg. Telamonia .

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Spherical fuzzy evidential reasoning for vehicle-to-grid enabled electric vehicle adoption: A data-driven analysis of public perception - Muhammad Zahid; Ezzeddin Bakhtavar; Salim Khoso; Syed Naveel Hussain; Rehan Sadiq; Kasun Hewage (Travel Behaviour and Society, 2026)

Synthesis of nano-ferrites-based materials: A new paradigm for electrochemical sensors - Sajjad Hussain; Imamdin Chandio; Md Abdur Rashid; Imran Sadiq; Jameel Ahmed Baig; Shakoor Ahmed Solangi; Muhammad Shahbaz; Khalid Hussain Thebo (Journal of Environmental Chemical Engineering, 2025)

Enhancing environmental quality and mitigating climate change: a renewable energy policy perspective based on evidence from most polluted European countries - Muhammad Sadiq; Muhammad Atif Nawaz; Fengsheng Chien; Arshian Sharif; Sobia Hanif (Gondwana Research, 2025)

Optimizing hybrid insulation systems for diverse climates: A comparative analysis of composite material combinations in residential buildings - Salim Khoso; Ezzeddin Bakhtavar; Ahmed Abouyoussef; Muhammad Zahid; Kasun Hewage; Rehan Sadiq (Energy and Buildings, 2025)

Investigating the Effect of Sn and Pt Doping and Co-doping on the Photocatalytic Efficiency of Zirconia for Degradation of Acid Yellow-76 - Mian Hussain Shah; Saima Sadiq; Umar Wahab; Inam Ullah; Sardar Hussain; Nasr Ullah; Safiullah Khan; Zaffar Iqbal; Muhammad Ismail; Aadil Nabi Chishti; Muhammad Sadiq (Water, Air, & Soil Pollution, 2025)

Cystic fibrosis in Pakistan: population harbouring rare variants non-responsive to CFTR modulators and the dilemma of poor health facilities - Anum Safdar; Muhammad Usman Ghani; Iqbal Bano; Tahir Mehmood; Hassan Rafique; Muhammad Farooq Sabar; Ali Akbar; Rehan Sadiq Shaikh (Molecular Biology Reports, 2025)

Evaluating citric and oxalic acids as sustainable chelating agents for heavy metal remediation and phytoextraction efficiency in contaminated soils using maize (Zea mays) - Ojone Anyebe; Fatihu Kabir Sadiq; Abdulalim Ahovi Sadiq; Khalid S. Almaary; Hafiz Muhammad Saleem Akhtar (Clean Technologies and Environmental Policy, 2025)

Fluoride contamination of groundwater in different geological settings of Punjab Province, Pakistan: Levels, possible mechanisms and health risks - Muhammad Sadiq; Syed Ali Musstjab Akber Shah Eqani; Ismat Nawaz; Nazneen Bangash; Shazia Ilyas; Joel Podgorski; Michael Berg (Science of The Total Environment, 2025)

Hybrid modeling of deep neural networks and unsupervised machine learning algorithms for missing well log prediction based on geological lithofacies similarities - Wakeel Hussain; Miao Luo; Muhammad Ali; Izhar Sadiq; Erasto E. Kasala; Tariq Aziz; Zuriyat Batool (Journal of Applied Geophysics, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Effect of sakuranetin against cyclophosphamide-induced immunodeficiency mice: role of IFN-γ/TNF-α/IgG/IgM/interleukins - Khalid Saad Alharbi; Sattam Khulaif Alenezi; Tariq Alsahli; Muhammad Afzal; Mohammad Jaffar Sadiq Mantargi; Imran Kazmi; Nadeem Sayyed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The role of mentorship in veterinary practice: An empirical study of the Animal Health Mentoring Framework in Pakistan - Ujala Fatima Shan; Aneela Zameer Durrani; Muhammad Zahid Iqbal; Shakera Sadiq Gill; Esha Binte Iqbal; Sadia Sanaullah; Muhammad Aftab; Mahrukh Ahmed; Safdar Aman (The Veterinary Journal, 2025)

A sustainable and cost-effective approach for efficient removal of Direct Blue-14 azo dye from wastewater using North American Zeolite for developing countries - Eman A. Al-Abbad; Rabia Rehman; Muhammad Sadiq Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

In-vitro, in-vivo and computational experiments for the antidiabetic potential of bioactive compound from Notholirion thomsonianum - Abdulaziz Hassan Alhasaniah; Abdul Sadiq; Ahmed Abdullah Al Awadh; Yahya I. Asiri; Meriem Rezigue; Rehman Zafar; Sajjad Ahmad; Muhammad Saeed Jan; Mater H. Mahnashi (Natural Product Research, 2025)

Trend analysis and performance of machine learning models for agroclimatology parameters in Bosso, Nigeria - Abubakar Sadiq Muhammad; Farid Zamani Che Rose; Muhammad Fadhil Marsani (Theoretical and Applied Climatology, 2025)

Fostering managers’ hope: A multi-analysis perspective on how green initiatives drive organizational performance - Mohd Adil; Syed Muhammad Fazel-e-Hasan; Hormoz Ahmadi; Mohd Sadiq; Harjit Sekhon; Alireza Amrollahi (Journal of Cleaner Production, 2025)

A review of recent advances in green and sustainable technologies for removing 4-nitrophenol from the water and wastewater - Hamza Badamasi; Zain Naeem; Giorgio Antoniolli; Avvaru Praveen Kumar; Abdul Ademola Olaleye; Ismail Shina Sadiq; Naseer Inuwa Durimin-iya; Muhammad Salman Khan (Sustainable Chemistry and Pharmacy, 2025)

Seasonal phytoplankton ecosystem dynamics in response to environmental variables in Winam Gulf, Lake Victoria, Kenya - Vincent Ochieng Suba; Muhammad Sadiq Khan; Jared Miruka; Lindsay Mwalati; Brian Njoroge; Emily Oluoch; John Nyongesa; Dennis Otieno; Yuelin Li (Aquatic Sciences, 2025)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

The impact of environmental, social, and governance (ESG) rating disparities on corporate risk: The mediating role of financing constraints - Xiaomin Bao; Muhammad Sadiq; Weiling Tye; Jing Zhang (Journal of Environmental Management, 2024)

Notes on species of Sporisorium and Ustilago from Pakistan - Sadiq Ullah; Najam-ul-Sehar Afshan; Aamna Ishaq; Maria Riaz; Muhammad Fiaz; Abdul Nasir Khalid; Mary Catherine Aime (Mycological Progress, 2024)

Role of quality assessment of the recycled packaging material in determining its safety profile as food contact material - Muhammad Rehan Khan; Muhammad Bilal Sadiq; Lukáš Vápenka; Stefania Volpe; Aleš Rajchl; Elena Torrieri (Waste Management, 2024)

Retraction Note: Dynamic nexus between transportation, urbanization, economic growth and environmental pollution in ASEAN countries: does environmental regulations matter? - Shi-Zheng Huang; Muhammad Sadiq; Fengsheng Chien (Environmental Science and Pollution Research, 2024)

Retraction Note: The impact of environmental knowledge and green supply chain practices in improving sustainable energy production: the moderating role of green behavior and green leadership - Shieh-Liang Chen; Yu-Sheng Su; Gia Luat Diep; Premagowrie Sivanandan; Muhammad Sadiq; Thi Thu Hien Phan (Environmental Science and Pollution Research, 2024)

Advanced AI approach for enhanced predictive modeling in reservoir characterization within complex geological environments - Wakeel Hussain; Muhammad Ali; Rakhshanda Sadaf; Harith F. Al-Khafaji; Izhar Sadiq; Chuanyu Hu; Hamza Daud; Salah Alshareef Alkfakey Ahmed (Modeling Earth Systems and Environment, 2024)

Soil erosion susceptibility mapping of Hangu Region, Kohat Plateau of Pakistan using GIS and RS-based models - Fakhrul Islam; Liaqat Ali Waseem; Tehmina Bibi; Waqar Ahmad; Muhammad Sadiq; Matee Ullah; Walid Soufan; Aqil Tariq (Journal of Mountain Science, 2024)

Retraction Note: Impact of credit, liquidity, and systematic risk on financial structure: comparative investigation from sustainable production - Muhammad Sadiq; Sami Alajlani; Muhammed Sajjad Hussain; Rashid Ahmad; Furrukh Bashir; Supat Chupradit (Environmental Science and Pollution Research, 2024)

Retraction Note: How green finance and financial development promote green economic growth: deployment of clean energy sources in South Asia - Muhammad Sadiq; Moataz Ahmad Amayri; Ch Paramaiah; Nguyen Hong Mai; Thanh Quang Ngo; Thi Thu Hien Phan (Environmental Science and Pollution Research, 2024)

Retraction Note: Testing role of green financing on climate change mitigation: Evidences from G7 and E7 countries - Xueying Wu; Muhammad Sadiq; Fengsheng Chien; Quang-Thanh Ngo; Anh-Tuan Nguyen; The-Truyen Trinh (Environmental Science and Pollution Research, 2024)

Retraction Note: Financing for energy efficiency solutions to mitigate opportunity cost of coal consumption: An empirical analysis of Chinese industries - Fengsheng Chien; YunQian Zhang; Muhammad Sadiq; Ching-Chi Hsu (Environmental Science and Pollution Research, 2024)

Geochemical insights of arsenic mobilization into the aquifers of Punjab, Pakistan - Muhammad Sadiq; Syed Ali Musstjab Akber Shah Eqani; Joel Podgorski; Shazia Ilyas; Syed Sayyam Abbas; Mustafa Nawaz Shafqat; Ismat Nawaz; Michael Berg (Science of The Total Environment, 2024)

Comparative influence of active PLA and PP films on the quality of minimally processed cherry tomatoes - Muhammad Rehan Khan; Lukas Vapenka; Muhammad Bilal Sadiq; Elena Torrieri; Ales Rajchl (Food Packaging and Shelf Life, 2024)

How does external debt and governance quality impact renewable energy consumption: novel policy insights from BRICS countries - Muhammad Sadiq; Besma Talbi; Sudeshna Ghosh; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2024)

Tapping the nutraceutical potential of industrial hemp against arthritis and diabetes - A comprehensive review - Allah Rakha; Hina Rasheed; Ammar B. Altemimi; Sidra Tul-Muntaha; Iraj Fatima; Masood Sadiq Butt; Saddam Hussain; Zuhaib F. Bhat; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Photovoltaic-integrated advancements for sustainable water production: Developing and evaluating an enhanced hybrid solar desalination system - Abubakar Sadiq Isah; Husna Bint Takaijudin; Balbir Singh Mahinder Singh; Tijani Oladoyin Abimbola; Muhammad Mujahid Muhammad; Sualawa Badruddeen Sani (Desalination, 2024)

An integrated perspective on fintech, green innovation and natural resource rent: Evidence from Asia - FengSheng Chien; YunQian Zhang; ZiQi Lin; YuChao Lin; Muhammad Sadiq (Resources Policy, 2024)

Genome-wide identification and in-silico expression analysis of CCO gene family in sunflower (Helianthus annuus) against abiotic stress - Adnan Sami; Muhammad Zeeshan Haider; Muhammad Shafiq; Saleh Sadiq; Farooq Ahmad (Plant Molecular Biology, 2024)
Carotenoid cleavage oxygenases (CCOs) enzymes play an important role in plant growth and development by producing a wide array of apocarotenoids and their derivatives. These compounds are vital for colouring flowers and fruits and synthesizing plant hormones such as abscisic acid and strigolactones. Despite their importance, the gene family responsible for CCO enzymes in sunflowers has not been identified. In this study, we identify the CCO genes of the sunflower plant to fill this knowledge gap. Phylogenetic and synteny analysis indicated that the Helianthus annuus CCO (HaCCO) genes were conserved in different plant species and they could be divided into three subgroups based on their conserved domains. Analysis using MEME tool and multiple sequence alignment identified conserved motifs in the HaCCO gene sequence. Cis -regulatory elements (CREs) analysis of the HaCCO genes indicated the presence of various responsive elements related to plant hormones, development, and responses to both biotic and abiotic stresses. This implies that these genes may respond to plant hormones, developmental cues, and drought stress, offering potential applications in the development of more resistant crops. Genes belonging to the 9-cis-epoxy carotenoid dioxygenases (NCED) subgroups predominantly exhibited chloroplast localization, whereas the genes found in other groups are primarily localized in the cytoplasm. These 21 identified HaCCOs were regulated by 60 miRNAs, indicating the crucial role of microRNAs in gene regulation in sunflowers. Gene expression analysis under drought stress revealed significant up-regulation of HaNCED16 and HaNCED19 , genes that are pivotal in ABA hormone biosynthesis. During organ-specific gene expression analysis, HaCCD12 and HaCCD20 genes exhibit higher activity in leaves, indicating a potential role in leaf pigmentation. This study provides a foundation for future research on the regulation and functions of the CCO gene family in sunflower and beyond. There is potential for developing molecular markers that could be employed in breeding programs to create new sunflower lines resistant to biotic and abiotic stresses.

Isolation, invitro, invivo anti-inflammatory, analgesic and antioxidant potential of Habenaria plantegania Lindl - Osama M. Alshehri; Madeeha Shabnam; Saeed Ahmed Asiri; Mater H. Mahnashi; Abdul Sadiq; Muhammad Saeed Jan (Inflammopharmacology, 2024)

Effect of fire and post-fire management on soil microbial communities in a lower subtropical forest ecosystem after a mountain fire - Mengmeng Yang; Xuan Luo; Ying Cai; Brian N. Mwangi; Muhammad Sadiq Khan; Fasih Ullah Haider; Wanxuan Huang; Xianli Cheng; Zefan Yang; Hongen Zhou; Shizhong Liu; Qianmei Zhang; et al. (Journal of Environmental Management, 2024)

Role of fintech, green finance, and natural resource rents in sustainable climate change in China. Mediating role of environmental regulations and government interventions in the pre-post COVID eras - Muhammad Sadiq; Ch Paramaiah; Robinson joseph; Ziguang Dong; Muhammad Atif Nawaz; Nizomjon Khajimuratov Shukurullaevich (Resources Policy, 2024)

Seaweed Application Enhanced the Growth and Yield of Pea (Pisum sativum L.) by Altering Physiological Indices - Safina Naz; Hafiza Muniba Din Muhammad; Muhammad Ramzan; Bushra Sadiq; Riaz Ahmad; Saqib Ali; Abdulaziz Abdullah Alsahli; Muhammad Ahsan Altaf (Journal of Soil Science and Plant Nutrition, 2023)

Variations in Surface Urban Heat Island and Urban Cool Island Intensity: A Review Across Major Climate Zones - Muhammad Sadiq Khan; Sami Ullah; Liding Chen (Chinese Geographical Science, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

Role of renewable and non-renewable energy consumption in environmental quality and their subsequent effects on average temperature: an assessment of sustainable development goals in South Korea - Waqar Ali Ather Bukhari; Amber Pervaiz; Mahwish Zafar; Muhammad Sadiq; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2023)

Green finance policy and heavy pollution enterprises: a supply-chain and signal transmission of green credit policy for the environment—Vietnam perspective - Chun-Wei Chen; Junxiong Zheng; Tin-Chang Chang; Muhammad Sadiq; Bushra Tufail (Environment, Development and Sustainability, 2023)

Metamorphism of Ladakh Island Arc terrain in the Himalayan region: implications from sulfide geochemistry and petrography - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Tao Wu; Zaheen Ullah; Syed Ali Turab; Tehseen Zafar; Zahid Hussain; Izhar Sadiq; Mubasir Ali (Arabian Journal of Geosciences, 2023)

Role of community-based conservation and natural resource management in building climate resilience among vulnerable mountain societies - Shameen Zafar; Muhammad Zafar Khan; Tahir Mehmood; Farida Begum; Maryam Sadiq (Climate and Development, 2023)

Natural resources: A determining factor of geopolitical risk in Russia? Revisiting conflict-based perspective - Lijun Pan; Yangjie Wang; Xiaofei Sun; Muhammad Sadiq; Abd Alwahed Dagestani (Resources Policy, 2023)

Unveiling the relationship between environmental quality, non-renewable energy usage and natural resource rent: Fresh insights from ten asian economies - Muhammad Sadiq; Kavita Chavali; V.V. Ajith Kumar; Kuan-Ting Wang; Phong Thanh Nguyen; Thanh Quang Ngo (Resources Policy, 2023)

The role of natural resources and eco-financing in producing renewable energy and carbon neutrality: Evidence from ten Asian countries - Ka Yin Chau; Muhammad Sadiq; FengSheng Chien (Resources Policy, 2023)

What role financial inclusion, green trade and natural resources utilization play in ASEAN economic growth: Evidence from post COVID era - Pham Van Kien; Jenho Peter Ou; Dr Muhammad Sadiq; Tran Thai Ha Nguyen; Pham Quang Huy; Trung Kien Tran (Resources Policy, 2023)

Policy uncertainty, renewable energy, corruption and CO2 emissions nexus in BRICS-1 countries: a panel CS-ARDL approach - Muhammad Sadiq; Syed Tauseef Hassan; Irfan Khan; Mohammad Mafizur Rahman (Environment, Development and Sustainability, 2023)

A step toward sustainable development: the nexus of environmental sustainability, technological advancement and green finance: evidence from Indonesia - FengSheng Chien; Ching-Chi Hsu; Massoud Moslehpour; Muhammad Sadiq; Bushra Tufail; Thanh Quang Ngo (Environment, Development and Sustainability, 2023)

The role of sustainable energy utility, natural resource utilization and waste management in reducing energy poverty: Evidence from South Asian countries - Fengsheng Chien; Muhammad Sadiq; Li Li; Arshian Sharif (Utilities Policy, 2023)

Dynamic correlated effects of electricity prices, biomass energy, and technological innovation in Tunisia's energy transition - Siying Li; Javier Cifuentes-Faura; Besma Talbi; Muhammad Sadiq; Kamel Si Mohammed; Muhammad Farhan Bashir (Utilities Policy, 2023)

The role of green finance in mitigating environmental degradation: Empirical evidence and policy implications from complex economies - Umar Numan; Benjiang Ma; Muhammad Sadiq; Hayat Dino Bedru; Can Jiang (Journal of Cleaner Production, 2023)

Toxic effects of cadmium on the physiological and biochemical attributes of plants, and phytoremediation strategies: A review - Yanliang Li; Shafeeq Ur Rahman; Zhixin Qiu; Sher Muhammad Shahzad; Muhammad Farrakh Nawaz; Jianzhi Huang; Sadiq Naveed; Lei Li; Xiaojie Wang; Hefa Cheng (Environmental Pollution, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Fluid source and physicochemical conditions of the polymetallic mineralization in Gawuch Formation, Kohistan Island Arc, NW Pakistan - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Dieter Garbe-Schönberg; Tao Wu; Zaheen Ullah; Zahid Hussain; Tehseen Zafar; Izhar Sadiq; Syed Wajid Hanif Bukhari; et al. (Geochemistry, 2023)

RETRACTED ARTICLE: The impact of environmental knowledge and green supply chain practices in improving sustainable energy production: the moderating role of green behavior and green leadership - Shieh-Liang Chen; Yu-Sheng Su; Gia Luat Diep; Premagowrie Sivanandan; Muhammad Sadiq; Thi Thu Hien Phan (Environmental Science and Pollution Research, 2023)

Impact of climate mitigation technology and natural resource management on climate change in China - FengSheng Chien; Ka Yin Chau; Muhammad Sadiq (Resources Policy, 2023)

Nexus of natural resources, urbanization and economic recovery in Asia: The moderating role of innovation - Liu xin; Trong Lam Vu; Thi Thu Hien Phan; Muhammad Sadiq; Nguyen Thi My Xuyen; Thanh Quang Ngo (Resources Policy, 2023)

Recent Advances, Future Trends, Applications and Challenges of Internet of Underwater Things (IoUT): A Comprehensive Review - Syed Agha Hassnain Mohsan; Yanlong Li; Muhammad Sadiq; Junwei Liang; Muhammad Asghar Khan (Journal of Marine Science and Engineering, 2023)
Oceans cover more than 70% of the Earth’s surface. For various reasons, almost 95% of these areas remain unexplored. Underwater wireless communication (UWC) has widespread applications, including real-time aquatic data collection, naval surveillance, natural disaster prevention, archaeological expeditions, oil and gas exploration, shipwreck exploration, maritime security, and the monitoring of aquatic species and water contamination. The promising concept of the Internet of Underwater Things (IoUT) is having a great influence in several areas, for example, in small research facilities and average-sized harbors, as well as in huge unexplored areas of ocean. The IoUT has emerged as an innovative technology with the potential to develop a smart ocean. The IoUT framework integrates different underwater communication techniques such as optical, magnetic induction, and acoustic signals. It is capable of revolutionizing industrial projects, scientific research, and business. The key enabler technology for the IoUT is the underwater wireless sensor network (UWSN); however, at present, this is characterized by limitations in reliability, long propagation delays, high energy consumption, a dynamic topology, and limited bandwidth. This study examines the literature to identify potential challenges and risks, as well as mitigating solutions, associated with the IoUT. Our findings reveal that the key contributing elements to the challenges facing the IoUT are underwater communications, energy storage, latency, mobility, a lack of standardization, transmission media, transmission range, and energy constraints. Furthermore, we discuss several IoUT applications while highlighting potential future research directions.

New trends in immunocastration and its potential to improve animal welfare: a mini review - Sohail Ahmed; Xunping Jiang; Guiqiong Liu; Amber Sadiq; Umar Farooq; Teketay Wassie; Ali Haider Saleem; Muhammad Zubair (Tropical Animal Health and Production, 2022)

Sub-acute toxicity study on hydromethanolic leaves extract of Combretum hypopilinum (Combretaceae) Diels in Wistar rats - Mubarak Hussaini Ahmad; Abdulkadir Umar Zezi; Sherifat Bola Anafi; Omar Yahya Alshargi; Mustapha Mohammed; Sagir Mustapha; Auwal Adam Bala; Surajuddeen Muhammad; Sa’adatu Muhammad Julde; Abubakar Sadiq Wada; Abubakar Ibrahim Jatau (Toxicological Research, 2022)

Selective Removal of Reactive Orange 16 via Adsorption onto Activated Alumina, and Its Application to Textile Wastewater - Naseem Rauf; Subah Sadiq Tahir; Chang Yoon-Seok; Shafqat Ullah; Muhammad Farooq (International Journal of Environmental Research, 2022)

RETRACTED ARTICLE: How green finance and financial development promote green economic growth: deployment of clean energy sources in South Asia - Muhammad Sadiq; Moataz Ahmad Amayri; Ch Paramaiah; Nguyen Hong Mai; Thanh Quang Ngo; Thi Thu Hien Phan (Environmental Science and Pollution Research, 2022)

Xylitol Production from Sugarcane Bagasse Through Ultrasound-Assisted Alkaline Pretreatment and Enzymatic Hydrolysis Followed by Fermentation - Sabitri Siris Thapa; Smriti Shrestha; Muhammad Bilal Sadiq; Anil Kumar Anal (Sugar Tech, 2022)

Enhanced photocatalytic potential of TiO2 nanoparticles in coupled CdTiO2 and ZnCdTiO2 nanocomposites - Shakeel Khan; Muhammad Sadiq; Niaz Muhammad (Environmental Science and Pollution Research, 2022)

Change in forest biomass with altitudinal variations in dry temperate forest of Dir Kohistan, Pakistan - Syed Tufail Ahmad; Ahmad Hussain; Saif Ullah; Aitezaz Muhammad Khan; Muhammad Sadiq Khan; Inam Ullah (Modeling Earth Systems and Environment, 2022)

An outlook on the development of renewable energy, policy measures to reshape the current energy mix, and how to achieve sustainable economic growth in the post COVID-19 era - Muhammad Farhan Bashir; Muhammad Sadiq; Besma Talbi; Luqman Shahzad; Muhammad Adnan Bashir (Environmental Science and Pollution Research, 2022)

How COVID-19 induced panic on stock price and green finance markets: global economic recovery nexus from volatility dynamics - Luc Phan Tan; Muhammad Sadiq; Talla M. Aldeehani; Syed Ehsanullah; Putri Mutira; Hieu Minh Vu (Environmental Science and Pollution Research, 2022)

Systematic analysis of HD-ZIP transcription factors in sesame genome and gene expression profiling of SiHD-ZIP class I entailing drought stress responses at early seedling stage - Maryam Mehmood; Muhammad Jadoon Khan; Muhammad Jawad Khan; Nadeem Akhtar; Fizza Mughal; Syed Tahir Abbas Shah; Muhammad Zeeshan Hyder; Sumaira Farrakh; Irfan Sadiq (Molecular Biology Reports, 2022)

RETRACTED ARTICLE: Impact of credit, liquidity, and systematic risk on financial structure: comparative investigation from sustainable production - Muhammad Sadiq; Sami Alajlani; Muhammed Sajjad Hussain; Rashid Ahmad; Furrukh Bashir; Supat Chupradit (Environmental Science and Pollution Research, 2022)

Staged energy and water quality optimization for large water distribution systems - Muhammad Nadeem Sharif; Ezzeddin Bakhtavar; Husnain Haider; Guangji Hu; Kasun Hewage; Rehan Sadiq (Environmental Monitoring and Assessment, 2022)

Green energy security assessment in Morocco: green finance as a step toward sustainable energy transition - Fatima Zahra Ainou; Mohsin Ali; Muhammad Sadiq (Environmental Science and Pollution Research, 2022)

Investigation of landslides with natural lineaments derived from integrated manual and automatic techniques applied on geospatial data - Simon Sadiq; Umar Muhammad; Michael Fuchs (Natural Hazards, 2022)

Effect of insect growth regulators and the fungi Beauveria bassiana (Bals.) alone and in combination on the larvae of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) in different cereals - Muhammad Awais Sadiq; Muhammad Afzal; Abu Bakar Muhammad Raza; Muhammad Irfan Ullah (International Journal of Tropical Insect Science, 2022)

RETRACTED ARTICLE: Financing for energy efficiency solutions to mitigate opportunity cost of coal consumption: An empirical analysis of Chinese industries - Fengsheng Chien; YunQian Zhang; Muhammad Sadiq; Ching-Chi Hsu (Environmental Science and Pollution Research, 2022)

COVID-19 fear and volatility index movements: empirical insights from ASEAN stock markets - Muhammad Sadiq; Ching-Chi Hsu; YunQian Zhang; Fengsheng Chien (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Testing role of green financing on climate change mitigation: Evidences from G7 and E7 countries - Xueying Wu; Muhammad Sadiq; Fengsheng Chien; Quang-Thanh Ngo; Anh-Tuan Nguyen; The-Truyen Trinh (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Dynamic nexus between transportation, urbanization, economic growth and environmental pollution in ASEAN countries: does environmental regulations matter? - Shi-Zheng Huang; Muhammad Sadiq; Fengsheng Chien (Environmental Science and Pollution Research, 2021)

The impact of natural resource rent, financial development, and urbanization on carbon emission - Shi-Zheng Huang; Muhammad Sadiq; Fengsheng Chien (Environmental Science and Pollution Research, 2021)

Survey of antibodies to Rift Valley fever virus and associated risk factors in one-humped camels (Camelus dromedarius) slaughtered in Maiduguri abattoir, Borno State, Nigeria - Hassan Ismail Musa; Caleb Ayuba Kudi; Muhammad Mamman Gashua; Abubakar Sadiq Muhammad; Abdulyeken Olawale Tijjani; Adamu Saleh Saidu; Sani Mohammed; Saleh Mohammed Jajere; Shuaibu Gidado Adamu (Tropical Animal Health and Production, 2021)

How energy insecurity leads to energy poverty? Do environmental consideration and climate change concerns matters - Syed Ehsanullah; Quyen Ha Tran; Muhammad Sadiq; Shahid Bashir; Muhammad Mohsin; Robina Iram (Environmental Science and Pollution Research, 2021)

Molecular detection and prevalence of Theileria ovis and Anaplasma marginale in sheep blood samples collected from Layyah district in Punjab, Pakistan - Kainat Abid; Sundas Bukhari; Muhammad Asif; Ayesha Sattar; Maryam Arshad; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Tropical Animal Health and Production, 2021)

Combining Landsat-8 spectral bands with ancillary variables for land cover classification in mountainous terrains of northern Pakistan - Arif Ur Rehman; Sami Ullah; Muhammad Shafique; Muhammad Sadiq Khan; Muhammad Tariq Badshah; Qi-jing Liu (Journal of Mountain Science, 2021)

Co-movement of energy prices and stock market return: environmental wavelet nexus of COVID-19 pandemic from the USA, Europe, and China - FengSheng Chien; Muhammad Sadiq; Hafiz Waqas Kamran; Muhammad Atif Nawaz; Muhammed Sajjad Hussain; Muhammad Raza (Environmental Science and Pollution Research, 2021)

Chemical composition of gemstones and characterization of their host pegmatites and country rocks from Chumar Bakhoor, Gilgit-Baltistan, Pakistan: implications for the source of gem-forming fluids - Amjad Hussain; Muhammad Tahir Shah; Mohammad Arif; Muhammad Hassan Agheem; Muhammad Saleem Mughal; Shakir Ullah; Syed Asim Hussain; Izhar Sadiq (Arabian Journal of Geosciences, 2021)

Comparing different space-borne sensors and methods for the retrieval of land surface temperature - Arif UR Rehman; Sami Ullah; Qijing Liu; Muhammad Sadiq Khan (Earth Science Informatics, 2021)

Estimation of data-driven streamflow predicting models using machine learning methods - Tanveer Ahmed Siddiqi; Saima Ashraf; Sadiq Ali Khan; Muhammad Jawed Iqbal (Arabian Journal of Geosciences, 2021)

Detection of focal and non-focal EEG signals using non-linear features derived from empirical wavelet transform rhythms - Hesam Akbari; Muhammad Tariq Sadiq (Physical and Engineering Sciences in Medicine, 2021)

Enhancement of photocatalytic potential and recoverability of Fe3O4 nanoparticles by decorating over monoclinic zirconia - Idrees Khan; Noor Zada; Ibrahim Khan; Muhammad Sadiq; Khalid Saeed (Journal of Environmental Health Science and Engineering, 2020)

Foliage application and seed priming with nitric oxide causes mitigation of salinity-induced metabolic adversaries in broccoli (Brassica oleracea L.) plants - Nudrat Aisha Akram; Naima Hafeez; Muhammad Farid-ul-Haq; Abrar Ahmad; Muhammad Sadiq; Muhammad Ashraf (Acta Physiologiae Plantarum, 2020)

Comparing the potential of stereo aerial photographs, stereo very high-resolution satellite images, and TanDEM-X for estimating forest height - Sami Ullah; Matthias Dees; Pawan Datta; Petra Adler; Tahir Saeed; Muhammad Sadiq Khan; Barbara Koch (International Journal of Remote Sensing, 2020)

Spicing up gastrointestinal health with dietary essential oils - Mahwish Tanveer; Charles Wagner; Muhammad Ikram ul Haq; Nilton C. Ribeiro; Thriumurugan Rathinasabapathy; Masood Sadiq Butt; Aamir Shehzad; Slavko Komarnytsky (Phytochemistry Reviews, 2020)

Assessment of subsurface lithology, groundwater depth, and quality of UET Lahore, Pakistan, using electrical resistivity method - Zahid Mehmood; Noor Muhammad Khan; Shamsher Sadiq; Saeed-ullah Jan Mandokhail; Syed Zishan Ashiq (Arabian Journal of Geosciences, 2020)

First Report Regarding the Simultaneous Molecular Detection of Anaplasma marginale and Theileria annulata in Equine Blood Samples Collected from Southern Punjab in Pakistan - Muhammad Asif; Asia Parveen; Sehrish Ashraf; Mureed Hussain; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Acta Parasitologica, 2020)

Alpha-Tocopherol-Induced Regulation of Growth and Metabolism in Plants Under Non-stress and Stress Conditions - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf; Fahad Al-Qurainy; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2019)

Economic assessment and ranking of wind power potential using fuzzy-TOPSIS approach - Muhammad Mohsin; Jijian Zhang; Rahman Saidur; Huaping Sun; Sadiq Mohammed Sait (Environmental Science and Pollution Research, 2019)

Trehalose: A Key Organic Osmolyte Effectively Involved in Plant Abiotic Stress Tolerance - Firdos Kosar; Nudrat Aisha Akram; Muhammad Sadiq; Fahad Al-Qurainy; Muhammad Ashraf (Journal of Plant Growth Regulation, 2019)

Manganese dioxide nanoparticles/activated carbon composite as efficient UV and visible-light photocatalyst - Idrees Khan; Muhammad Sadiq; Ibrahim Khan; Khalid Saeed (Environmental Science and Pollution Research, 2019)

Effect of distillery spentwash fertigation on crop growth, yield, and accumulation of potentially toxic elements in rice - Sadiq Naveed; Abdur Rehim; Muhammad Imran; Muhammad Faraz Anwar; Saddam Hussain (Environmental Science and Pollution Research, 2018)

Mesorhizobium hankyongi sp. nov. Isolated from Soil of Ginseng Cultivating Field - Muhammad Zubair Siddiqi; Sadiq Shah; Kang Duk Choi; Soon Youl Lee; Sang Young Kim; Wan-Taek Im (Current Microbiology, 2018)

Impact of exogenously applied tocopherol on some key physio-biochemical and yield attributes in mungbean [Vigna radiata (L.) Wilczek] under limited irrigation regimes - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf (Acta Physiologiae Plantarum, 2018)

Resveratrol as an anti-cancer agent: A review - Abdur Rauf; Muhammad Imran; Masood Sadiq Butt; Muhammad Nadeem; Dennis G. Peters; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2018)

Therapeutic potential of dairy bioactive peptides: A contemporary perspective - Saira Sultan; Nuzhat Huma; Masood Sadiq Butt; Muhammad Aleem; Munawar Abbas (Critical Reviews in Food Science and Nutrition, 2018)

Rice bran nutraceutics: A comprehensive review - Muhammad Sohail; Allah Rakha; Masood Sadiq Butt; Muhammad Jawad Iqbal; Summer Rashid (Critical Reviews in Food Science and Nutrition, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

High-resolution regional gravity field model of Pakistan based on best residual terrain model (RTM) of topography and interpolation techniques - Muhammad Sadiq; Aneeque A. Qazi; M. Ramzan (Arabian Journal of Geosciences, 2017)

A whole-body physiologically based pharmacokinetic (WB-PBPK) model of ciprofloxacin: a step towards predicting bacterial killing at sites of infection - Muhammad W. Sadiq; Elisabet I. Nielsen; Dalia Khachman; Jean-Marie Conil; Bernard Georges; Georges Houin; Celine M. Laffont; Mats O. Karlsson; Lena E. Friberg (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Examination of CK2α and NF-κB p65 expression in human benign prostatic hyperplasia and prostate cancer tissues - Fatima Qaiser; Janeen H. Trembley; Sarah Sadiq; Iqbal Muhammad; Rubina Younis; Shoaib Naiyar Hashmi; Badar Murtaza; Thomas S. Rector; Abdul Khaliq Naveed; Khalil Ahmed (Molecular and Cellular Biochemistry, 2016)

Molecular characterization and growth optimization of halo-tolerant protease producing Bacillus Subtilis Strain BLK-1.5 isolated from salt mines of Karak, Pakistan - Nawab Ali; Nimat Ullah; Muhammad Qasim; Hazir Rahman; Shahid Niaz Khan; Abdul Sadiq; Muhammad Adnan (Extremophiles, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Phenolic, flavonoid contents, anticholinesterase and antioxidant evaluation of Iris germanica var ; florentina - Farhat Ullah; Muhammad Ayaz; Abdul Sadiq; Abid Hussain; Sajjad Ahmad; Muhammad Imran; Anwar Zeb (Natural Product Research, 2016)

The use of FAMACHA in estimation of gastrointestinal nematodes and total worm burden in Damara and Barbados Blackbelly cross sheep - Konto Mohammed; Yusuf Abba; Nur Syairah Binti Ramli; Murugaiyah Marimuthu; Mohammed Ariff Omar; Faez Firdaus Jesse Abdullah; Muhammad Abubakar Sadiq; Abdulnasir Tijjani; Eric Lim Teik Chung; Mohammed Azmi Mohammed Lila (Tropical Animal Health and Production, 2016)

An optimal approach for the development of precise regional geoid in Pakistan through a comparative study with least square collocation and FFT techniques - Sadiq Muhammad; Ahmad Zulfiqar (Arabian Journal of Geosciences, 2015)

Tomato ( Solanum lycopersicum ) Carotenoids and Lycopenes Chemistry; Metabolism, Absorption, Nutrition, and Allied Health Claims—A Comprehensive Review - Rashida Perveen; Hafiz Ansar Rasul Suleria; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Sarfraz Ahmad (Critical Reviews in Food Science and Nutrition, 2015)

Heterogeneous data management and modeling for the gravimetric geoid model: a review study in Pakistan - Muhammad Sadiq; Zulfiqar Ahmad (Arabian Journal of Geosciences, 2015)

Protein–Energy Malnutrition: A Risk Factor for Various Ailments - Rizwana Batool; Masood Sadiq Butt; Muhammad Tauseef Sultan; Farhan Saeed; Rabia Naz (Critical Reviews in Food Science and Nutrition, 2015)

Onion: Nature Protection Against Physiological Threats - Hafiz Ansar Rasul Suleria; Masood Sadiq Butt; Faqir Muhammad Anjum; Farhan Saeed; Nauman Khalid (Critical Reviews in Food Science and Nutrition, 2015)

Rice Bran: A Novel Functional Ingredient - Mian Kamran Sharif; Masood Sadiq Butt; Faqir Muhammad Anjum; Saima Hafiz Khan (Critical Reviews in Food Science and Nutrition, 2014)

Black Pepper and Health Claims: A Comprehensive Treatise - Masood Sadiq Butt; Imran Pasha; Muhammad Tauseef Sultan; Muhammad Atif Randhawa; Farhan Saeed; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2013)

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies - Muhammad Abrar; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Muhammad Atif Randhawa; Farhan Saeed; Khalid Waqas (Critical Reviews in Food Science and Nutrition, 2013)

Toxic Effect of Nickel (Ni) on Growth and Metabolism in Germinating Seeds of Sunflower (Helianthus annuus L.) - Muhammad Yasin Ashraf; Rumana Sadiq; Mumtaz Hussain; Muhammad Ashraf; M. Sajid Aqeel Ahmad (Biological Trace Element Research, 2011)

Nigella sativa : Reduces the Risk of Various Maladies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2010)

Isolation and synthesis of flavonols and comparison of their antioxidant activity - Aurangzeb Hasan; A. Sadiq; A. Abbas; E. Mughal; Khalid M. Khan; Muhammad Ali (Natural Product Research, 2010)

Vertical gravity anomaly gradient effect of innermost zone on geoid-quasigeoid separation and an optimal integration radius in planar approximation - Sadiq Muhammad; Ahmad Zulfiqar; Ayub Muhammad (Applied Geomatics, 2010)

An estimation of the height system bias parameter N 0 using least squares collocation from observed gravity and GPS-levelling data - Muhammad Sadiq; Carl C. Tscherning; Zulfiqar Ahmad (Studia Geophysica et Geodaetica, 2009)

Garlic: Nature's Protection Against Physiological Threats - Masood Sadiq Butt; Muhammad Tauseef Sultan; Mehmood S. Butt; Javaid Iqbal (Critical Reviews in Food Science and Nutrition, 2009)

Green Tea: Nature's Defense against Malignancies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2009)

Geochemical Behavior of Arsenic in Kelly Lake, Ontario - Muhammad Sadiq; Allen Locke; Grame Spiers; David A. B. Pearson (Water, Air, & Soil Pollution, 2002)

Arsenic chemistry in soils: An overview of thermodynamic predictions and field observations - Muhammad Sadiq (Water, Air, & Soil Pollution, 1997)

Arsenic Chemistry in Soils: An Overview of Thermodynamic Predictions and Field Observations - Muhammad Sadiq (Water, Air, & Soil Pollution, 1997)